2019
DOI: 10.1186/s12052-019-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

The nature of science as a foundation for fostering a better understanding of evolution

Abstract: Misunderstandings of the nature of science (NOS) contribute greatly to resistance to evolutionary theory especially among non-scientific audiences. Here we delineate three extended instructional examples that make extensive use of NOS to establish a foundation upon which to more successfully introduce evolution. Specifically, these instructional examples enable students to consider evolutionary biology using NOS as a lens for interpretation of evolutionary concepts. We have further found, through our respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 86 publications
0
30
0
1
Order By: Relevance
“…A multifactorial analysis by Dunk et al ( 2017 ) suggested that out of factors including evolutionary content knowledge, religiosity, epistemological sophistication, and an understanding of the nature of science, the latter was the most important factor associated with acceptance of evolution amongst college students, explaining four times more variation than evolutionary content knowledge. Nelson et al ( 2019 ) argue that teaching the nature of science may be the most effective tool to increasing understanding of evolution. Additional work (Rutledge and Warden 2000 ; Rosengren et al 2012 ; Akyol et al 2010 ; Cavallo 2008 ; Lombrozo et al 2008 ) has also found a connection between an understanding of NOS and acceptance of evolutionary theory.…”
Section: Teaching the Nature Of Sciencementioning
confidence: 99%
“…A multifactorial analysis by Dunk et al ( 2017 ) suggested that out of factors including evolutionary content knowledge, religiosity, epistemological sophistication, and an understanding of the nature of science, the latter was the most important factor associated with acceptance of evolution amongst college students, explaining four times more variation than evolutionary content knowledge. Nelson et al ( 2019 ) argue that teaching the nature of science may be the most effective tool to increasing understanding of evolution. Additional work (Rutledge and Warden 2000 ; Rosengren et al 2012 ; Akyol et al 2010 ; Cavallo 2008 ; Lombrozo et al 2008 ) has also found a connection between an understanding of NOS and acceptance of evolutionary theory.…”
Section: Teaching the Nature Of Sciencementioning
confidence: 99%
“…A more promising approach may thus be to focus on people’s knowledge of general science facts and of the processes and practices of science, known as the Nature of Science (NoS). In general, people who have higher NoS knowledge may be in a better position to understand the connection between scientific practices and the generation of knowledge (Nelson et al, 2019; Thanukos and Scotchmoor, 2012) or the role that the scientific community plays (Slater et al, 2019). This knowledge may allow for more robust acceptance of the scientific consensus or greater trust in scientific claims.…”
Section: Measuring People’s Knowledge About the Nature Of Sciencementioning
confidence: 99%
“…My second through several subsequent attempts were much improved after several discussions with a key mentor, Craig E. Nelson, Emeritus Professor of Biology (Indiana University). Nelson implemented peer discussion as early as the mid-1970s and described the benefits of this pedagogy in promoting critical thinking (Nelson 1986, Nelson et al 1998, Nelson 2008Nelson et al 2019). Crucial to the success of peer discussion pedagogy is relevant subject matter and the establishment of structured guidelines for how peers should interact-what is off-limits and what should be encouraged-to facilitate the building of positive student-student relationships.…”
Section: Epilogue: Learning Across a Career To Establish Critical Relmentioning
confidence: 99%
“…Crucial to the successful critical thinking of undergraduate novice teacher candidates was explicit and reflective NOS and evolution assignments. The prominent tenets of which are delineated in Scharmann (2018) and Nelson et al (2019).…”
Section: Epilogue: Learning Across a Career To Establish Critical Relmentioning
confidence: 99%
See 1 more Smart Citation